Hip fractures are risky business: An analysis of the NSQIP data. Issue 4 (April 2015) - Sathiyakumar, Vasanth; Greenberg, Sarah E.; Molina, Cesar S.; Thakore, Rachel V.; Obremskey, William T.; Sethi, Manish K.
Abstract: Introduction: Hip fractures are one of the most common types of orthopaedic injury with high rates of morbidity. Currently, no study has compared risk factors and adverse events following the different types of hip fracture surgeries. The purpose of this paper is to investigate the major and minor adverse events and risk factors for complication development associated with five common surgeries for the treatment of hip fractures using the NSQIP database. Methods: Using the ACS-NSQIP database, complications for five forms of hip surgeries were selected and categorized into major and minor adverse events. Demographics and clinical variables were collected and an unadjusted bivariate logistic regression analyses was performed to determine significant risk factors for adverse events. Five multivariate regressions were run for each surgery as well as a combined regression analysis. Results: A total of 9640 patients undergoing surgery for hip fracture were identified with an adverse events rate of 25.2% ( n = 2433). Open reduction and internal fixation of a femoral neck fracture had the greatest percentage of all major events (16.6%) and total adverse events (27.4%), whereas partial hip hemiarthroplasty had the greatest percentage of all minor events (11.6%). Mortality was the most common major adverse event (44.9–50.6%). For minor complications, urinary tract infections were the most common minor adverse event (52.7–62.6%). Significant risk factors for development of any adverse event included age, BMI, gender, race, active smoking status, history of COPD, history of CHF, ASA score, dyspnoea, and functional status, with various combinations of these factors significantly affecting complication development for the individual surgeries. Conclusions: Hip fractures are associated with significantly high numbers of adverse events. The type of surgery affects the type of complications developed and also has an effect on what risk factors significantly predict the development of a complication. Concerted efforts from orthopaedists should be made to identify higher risk patients and prevent the most common adverse events that occur postoperatively.